2011
DOI: 10.1002/adma.201103220
|View full text |Cite
|
Sign up to set email alerts
|

A Multiresponsive, Shape‐Persistent, and Elastic Supramolecular Polymer Network Gel Constructed by Orthogonal Self‐Assembly

Abstract: A cross-linked supramolecular polymer network gel is designed and prepared, which shows reversible gel-sol transitions induced by changes in pH, temperature, cation concentration, and metal co-ordination. The gel pore size is controlled by the amount of cross-linker added to the system, and the material can be molded into shape-persistent, free-standing objects with elastic behavior. These features are all due to the dynamically reversible host-guest complexation and good mechanical properties of the cross-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
333
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 675 publications
(340 citation statements)
references
References 107 publications
7
333
0
Order By: Relevance
“…3, spectrum D). Above 20.0 mM, the peaks undergo broadening that obscures the well-resolved splitting associated with the free ligand and indicates the formation of high-molecular-weight rhombic aggregates (14,19). Despite these spectral changes in the 1 H NMR, the 31 P { 1 H} NMR spectra of 1 have no significant concentration dependencies, with the exception of some broadening that occurs at high concentrations (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…3, spectrum D). Above 20.0 mM, the peaks undergo broadening that obscures the well-resolved splitting associated with the free ligand and indicates the formation of high-molecular-weight rhombic aggregates (14,19). Despite these spectral changes in the 1 H NMR, the 31 P { 1 H} NMR spectra of 1 have no significant concentration dependencies, with the exception of some broadening that occurs at high concentrations (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…S30). DOSY was used to probe the dimensions of the polydispersed supramolecular aggregates (14,19). As the concentration of rhomboid 1 was increased between 10.0 and 90.0 mM, the measured weight average diffusion coefficient decreased from 1.07 × 10 −10 to 5.83 × 10 −12 m 2 ·s −1 (D 10.0 mM /D 90.0 mM ∼ 19; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supramolecular polymers can be defined as dynamically reversible polymeric arrays (29)(30)(31)(32)(33)(34)(35)(36)(37) that form from the explicit manipulation of noncovalent forces between monomeric units (38)(39)(40)(41)(42)(43). Supramolecular polymer chemistry can readily complement coordination-driven self-assembly, as exemplified by our efforts to design hierarchical supramolecular polymerizations of discrete organoplatinum(II) metallacycles, thus accessing novel supramolecular polymeric materials, such as macroscopic hexagonal supramolecular polymer fibers (44), dendronized organoplatinum(II) metallacyclic polymers (45), and a responsive, cavity-cored supramolecular polymer network metallogel (46).…”
mentioning
confidence: 99%
“…The fluorescent results showed that the assemblies displayed ratio-metric properties with the changes of aggregation-induced emission and monomer-emission, and fluorescence quenching with addition of Pd 2+ . Keywords tetraphenylethene; DB24C8; secondary ammonium ion; supramolecular polymer; aggregations-induced emission 将高分子聚合物与超分子化学相结合所形成的超 分子聚合物是近年来超分子化学领域的研究热点之 一 [8] Wavelength/nm …”
mentioning
confidence: 99%